Revisiting the amplification effect of induced disgust on moral judgments: An investigation of Japanese subjects - Matsuo, Akiko; Tanaka, Yuri; Mukai, Tomoya (Jikken shakai shinrigaku kenkyū, 2025)
Disgust is related to harsher moral judgments, which is known as the amplification effect. Previous studies have examined other effects (e.g., the cleansing effect) based on the assumption that the amplification effect exists. This is problematic if the amplification effect does not exist. Therefore, this study investigated the robustness of the amplification effect. We set two conditions (disgust vs. neutral), presented visual images, and subsequently asked the participants to make moral judgments. We compared the disgust and neutral conditions and observed significant differences in the amplification effect on moral judgments, although the effect sizes were relatively small. This study makes a valuable contribution to existing theories on disgust and morality, especially regarding methodology, and its findings may apply to the mechanisms of other related phenomena.